Answer:
Here we want to solve:
(cos(A) + sin(A))^2 + ( sin(A) - cos(A))^2 = 2
First, remember the two expansions:
(a + b)^2 = a^2 + 2*a*b + b^2
(a - b)^2 = a^2 - 2*a*b - b^2
Using these relations, we can expand:
(cos(A) + sin(A))^2 = cos(A)^2 + 2*cos(A)*sin(A) + sin(A)^2
( sin(A) - cos(A))^2 = sin(A)^2 - 2*sin(A)*cos(A) + cos(A)^2
Replacing that in our equation, we geT:
(cos(A)^2 + 2*cos(A)*sin(A) + sin(A)^2) + (sin(A)^2 - 2*sin(A)*cos(A) + cos(A)^2) = 2
We can simplify this to get:
2*cos(A)^2 + 2*sin(A)^2 + 2*cos(A)*sin(A) - 2*cos(A)*sin(A) = 2
2*cos(A)^2 + 2*sin(A)^2 = 2
We can take the 2 as a common factor to get:
2*cos(A)^2 + 2*sin(A)^2 = 2*( cos(A)^2 + sin(A)^2) = 2
Now we can divide both sides by 2:
2*( cos(A)^2 + sin(A)^2)/2 = 2/2
cos(A)^2 + sin(A)^2 = 1
And this is a trigonometric property that is true for any value of A.
So the equality:
(cos(A) + sin(A))^2 + ( sin(A) - cos(A))^2 = 2
is true for any real value of A.